Purification and characterization of an extracellular alpha-amylase from Clostridium perfringens type A. - Shih, N J (1995)
An alpha-amylase (EC 3.2.1.1) secreted by Clostridium perfringens NCTC 8679 type A was purified to homogeneity and characterized. It was isolated from concentrated cell-free culture medium by ion-exchange and gel permeation chromatography. The enzyme exhibited maximal activity at pH 6.5 and 30 degrees C without the presence of calcium. The pI of the enzyme was 4.75. The estimated molecular weight of the purified enzyme was 76 kDa. The purified enzyme was inactivated between 35 and 40 degrees C, which increased to between 45 and 50 degrees C in the presence of calcium (5 mM). The purified enzyme produced a mixture of oligosaccharides as major end products of starch hydrolysis, indicating alpha-amylase activity.